Advanced breast cancer rates in the epoch of service screening: The 400, 000 women cohort study from Italy. (April 2017) - ,; Manneschi, G.; Miccinesi, G.; Caranci, N.; Naldoni, C.; Finarelli, A.C.; Ferretti, S.; Pandolfi, P.; Pizzi, L.; Petrucci, C.; Baldazzi, P.; Pasquini, A.; et al.
Abstract: Background: The objective of this study was to evaluate if mammography screening attendance is associated with a reduction in late-stage breast cancer incidence. Methods: The cohort included over 400, 000 Italian women who were first invited to participate in regional screening programmes during the 1990s and were followed for breast cancer incidence for 13 years. We obtained individual data on their exposure to screening and correlated this with total and stage-specific breast cancer incidence. Socio-economic status and pre-screening incidence data were used to assess the presence of self-selection bias. Results: Overall, screening attendance was associated with a 10% excess risk of in situ and invasive breast cancer (IRR = 1.10; 95% confidence interval (CI): 1.06–1.14), which dropped to 5% for invasive cancers only (IRR = 1.05; 95% CI: 1.01–1.09). There were significant reductions among attenders for specific cancer stages; we observed a 39% reduction for T2 or larger (IRR = 0.61; 95% CI: 0.57–0.66), 19% for node positives (IRR = 0.81; 95% CI: 0.76–0.86) and 28% for stage II and higher (IRR = 0.72; 95% CI: 0.68–0.76). Our data suggest that the presence of self-selection bias is limited and, overall, invited women experienced a 17% reduction of advanced cancers compared with pre-screening rates. Conclusions: Comparing attenders' and non-attenders' stage-specific breast cancer incidence, we have estimated that screening attendance is associated with a reduction of nearly 30% for stages II+. Highlights: Efficacy of mammographic screening in reducing advanced breast cancer is questioned. We analysed a large cohort of 400, 000 Italian invited women followed for 13 years. Screening attendance is associated with a reduction of nearly 30% stage II+ rates. That reduction occurred although overall incidence is 5% higher among attenders.